The study of effectiveness of sound insulation and soundproofing in a classroom building in UiTM Shah Alam / Mohamad Irfan Mohamad Zaidi - Mohamad Zaidi, Mohamad Irfan (Faculty Architecture, Planninng and Surveying, 2014)
sound insulation and soundproofing in a classroom building. It was predetermined that some classrooms in UiTM Shah Alam are lacking in terms of sound insulation and soundproofing capabilities. In other words, sounds created from outside of the classroom can be easily heard from inside of the classroom. This is due to the fact that most classrooms in UiTM are not fully equipped with necessary sound control systems and sound insulating materials which can help reduce the level of noise inside the classroom. The lack of sound filter will allow noise to penetrate through the walls of the classroom with no difficulty which can cause noise disturbance inside the classroom. Needless to say, the exposure of noise towards the students can disrupt their learning process and lowers productivity. Which is why this research was carried out in order to identify the solution to the noise problem and to determine the best way to control noise. This also includes acoustic designs in a building. Also to determine the best approach to regulate the noise behavior, either controlling it at the source, at the path of transmission, or at the receiver. Moreover, the researcher is trying to figure out what type of acoustic materials and noise cancelling products to be used for the classroom. This research will be focusing on the classroom building in UiTM Shah Alam only. The research methodology that was chosen to be used for this research is the sound level test experiment and observation of the case study hat was chosen. The experiments involves the use of a sound level meter to measure the level of noise in the classrooms. Each classrooms readings was taken in specific intervals for each time period. After the data was obtained, it was compared and analyzed to obtain a finding. Based on the findings obtained, it is clear that there are variances in the noise level in accordance to the time and location of the classrooms which related to the acoustic insulation capabilities of the classroom.